Amplitude-only measurements of a dual open ended coaxial sensor system for determination of complex permittivity of materials - Lee, Kim Yee; Chung, Boon Kuan; Abbas, Zulkifly; You, Kok Yeow; Cheng, Ee Meng (EMW Publishing, 2013)
This paper describes a novel permittivity measurement technique using dual open ended coaxial sensors. The magnitudes of the reflection coefficient from two open ended coaxial sensors were used to determine complex reflection coefficients and permittivity of a sample under test.